IMPORTANCE OF TRAINING NEEDS ANALYSIS FOR HUMAN RESOURCES DEVELOPMENT IN ORGANIZATIONS - Shandy Puspita Puspita; Andres Dharma Nurhalim (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2021)
Human resources are the main element of an organization. To meet the need for good performance improvement in an organization, one of the ways that can be taken is by conducting training and human resource development. Pragmatically, training and development programs have a positive influence on both individuals and organizations. Training needs analysis is an activity that needs to be carried out systematically to find any gaps between the knowledge, skills and attitudes of a person needed by the organization that can be improved through training. This behavioral needs analysis will later assist the organization in using resources effectively and prevent unnecessary training activities.